MODEL PEMBELAJARAN REALISTIC MATEMATICS EDUCATION - Alani, Nabella (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2020)
The problem of mathematics learning in the schools is the level of mathematics literacy of students in Indonesia that is still very low. Conditions of learning mathematics according to the Program for International Student Assessment (PISA, 2015) 50.5% of Indonesian students have mathematical literacy skills below level 1. Ability below level 1 only solves math problems with one step, 27.6% is at level 1 that are being able to use simple formulas, procedures, and algorithms, being able to carry out literal interpretation and direct reasoning in solving mathematical problems. It takes an effort to learn mathematics that is realistic and constructivist. One of model that fulfills these two characteristics is discussed in this paper, in the context of Realistic Mathematics Education.